WOM antecedents in backpacker travelers - Alves, Sandra (2016)
This study examines the antecedents of Word-of-Mouth (WOM) message content (MC) of backpackers' travelers. How travel motivation, the sense of belonging, social interaction places and cultural activities influence WOM-MC in the case of backpacker travelers. The study tests a model empirically using a survey of 656 backpackers from 75 different countries.